2020
DOI: 10.1155/2020/3264525
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic Reticulum Stress Regulates Scleral Remodeling in a Guinea Pig Model of Form-Deprivation Myopia

Abstract: Purpose. This study aimed to investigate the role of endoplasmic reticulum (ER) stress in scleral remodeling in a guinea pig model of form-deprivation myopia (FDM). Methods. Guinea pigs were form deprived to induce myopia. ER ultrastructural changes in the sclera were examined by transmission electron microscopy (TEM). The protein levels of ER stress chaperones, including GRP78, CHOP, and calreticulin (CRT), were analyzed by western blotting at 24 hours, 1 week, and 4 weeks of FD. Scleral fibroblasts from guin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 48 publications
2
5
0
Order By: Relevance
“…The most common animal models of myopia are form-deprivation myopia (FDM) and lens-induced myopia (LIM) [ 2 4 ]. Recently, our team found that mice with LIM showed endoplasmic reticulum (ER) stress in the sclera, which is similar to the results of other researchers using the FDM model [ 5 , 6 ]. Furthermore, we previously showed that scleral ER stress causes myopia [ 5 , 6 ].…”
Section: Introductionsupporting
confidence: 86%
See 1 more Smart Citation
“…The most common animal models of myopia are form-deprivation myopia (FDM) and lens-induced myopia (LIM) [ 2 4 ]. Recently, our team found that mice with LIM showed endoplasmic reticulum (ER) stress in the sclera, which is similar to the results of other researchers using the FDM model [ 5 , 6 ]. Furthermore, we previously showed that scleral ER stress causes myopia [ 5 , 6 ].…”
Section: Introductionsupporting
confidence: 86%
“…Recently, our team found that mice with LIM showed endoplasmic reticulum (ER) stress in the sclera, which is similar to the results of other researchers using the FDM model [ 5 , 6 ]. Furthermore, we previously showed that scleral ER stress causes myopia [ 5 , 6 ]. This clearly indicates a correlation between myopia and ER stress.…”
Section: Introductionsupporting
confidence: 86%
“…The Col1a1 and Mmp2 genes have been reported to encode the extracellular matrix component collagen and are engaged in extracellular matrix remodeling in the sclera [31,32]. In addition, the proteins encoded by Col1a1 and Mmp2 are involved in angiogenesis and the myopia pathway (among other activities) in mice and guinea pigs [33][34][35][36]. Here, we found that the expression levels of these two genes were upregulated in the retina after the intravitreal injection of brimonidine.…”
Section: Discussionmentioning
confidence: 66%
“…We hypothesized that scleral ER stress participates in the onset and progression of axial elongation during the myopia development as axial elongation is a change in the organ size, which is probably achieved by remodeling of ECM in sclera. In fact, there have been recent reports indicating that ER stress occurs in the myopic sclera using a form-deprivation myopia model in guinea pig 15 . To elucidate the hypothesis, we used pharmacological and genetic methods to induce/inhibit ER stress in a mouse model of LIM and tested its effect on the myopia progression.…”
Section: Introductionmentioning
confidence: 99%